Analisis Kepuasan Konsumen Terhadap Kualitas Pelayanan Klinik Orthotik Prosthetik Kuspito Jaten Karanganyar - M Syafi’i (Interest : Jurnal Ilmu Kesehatan, 2016)
Abstract: The Balance, Arch Of The Foot. Clinic Orthotic Prosthetic Kuspito Karanganyar is a business organization engaged in health services facilities provided are of service in the manufacture of fake hands and feet (Orthotic Prosthetic). Orthotic clinic Prosthetik Kuspito is one of the few clinics in Indonesia. Large number of consumers who come to get service at the clinic Orthotic Prosthetic Kuspito, and its growing number of competitors particular region of Surakarta, the research is expected to know an idea of the quality of service making a false hand, artificial limbs and other mobility aids are offered Clinic Orthotic Prosthetic Kuspito and expectations and perceptions of consumers, and is expected to also obtain some information as input to the Clinic Orthotic Prosthetic Kuspito in order to improve the quality of care services to achieve customer satisfaction, increase consumer confidence, maintain and develop their businesses. The results of this study are to find out consumers' assessment of service quality and satisfaction that can be felt. This is important as a reference in order to service providing optimum satisfaction.